Study of Basic Theory of Nuclear Models: Exploring the Theoretical Foundations of Nuclear Models (Journal of Advances and Scholarly Researches in Allied Education, 2019)
In this paper, we will discuss about various nuclear models, their basic postulates as well as their limitations. The small size of nuclear and the fact that the forces concerned do not appear elsewhere, make the theoretical approach to nuclear structure more difficult than the theoretical approach to electronic structure. There are many isolated facts, which require explanation when we adopt any nuclear model. The characteristics of nuclear–nuclear forces in conjunction with Pauli exclusion principle cause nuclear matter to exhibit apparently contradictory behavior. The macroscopic properties, such as constant density, constant Binding energy per nucleon, resemble those of drop of a liquid. On the other hand the macroscopic properties such as nuclear wave functions and particle motions resemble those of weakly interacting gas. The resemblance to a drop of liquid serves as the basis for liquid drop model and collective model whereas resemblance to a weakly interacting gas serves as the basis for Fermi gas model and shell model.